Vasomotor reactions in the face and head of patients with migraine: A systematic review with perspectives to the facial skin disorder rosacea. (28th August 2018) - Wienholtz, Nita; Christensen, Casper Emil; Egeberg, Alexander; Thyssen, Jacob P; Ashina, Messoud
Objective: To systematically review extracranial vasomotor reactions in patients with migraine, and to discuss potential overlaps with rosacea. Background: Autonomic manifestations are common in migraine and may reflect trigeminovascular system activation. Flushing during migraine attacks may indicate altered extracranial vasomotor reactivity which resembles that of the facial skin disorder rosacea. Methods: PubMed and EMBASE were searched for studies investigating extracranial vascular reactions in migraine and rosacea published until January 2018. Results: We uncovered 41 studies investigating extracranial circulation in migraine and 12 studies in rosacea. Skin temperature was generally lower on the forehead, nose and hands of migraine patients compared to controls. The superficial temporal artery (STA) showed greater amplitude variations in migraine patients compared to controls, and compression of either the STA or the common carotid artery during attacks led to transient pain relief in about one-third of the investigated patients. Facial skin blood flow was asymmetrical in migraine patients compared to healthy volunteers. Conclusion: Findings on extracranial microcirculation suggest an altered function of the autonomic nervous system in migraine patients. Similar signs of autonomic nervous system dysfunction are reported in rosacea. We suggest an overlap in autonomic and neurovascular pathophysiology in migraine and rosacea.